Cost Efficiency of Green Infrastructure in Flash Flood Management: An Economic Model for Local Authorities (International Journal of Built Environment and Sustainability, 2025)
The gradual increase in the urbanization process over the years has increased the impervious surfaces while reducing green spaces, thereby contributing to the frequent occurrence of flash floods. The higher prevalence of flash foods has impacted the local authorities in spending huge amounts of costing for the purpose of repairing and cleaning the damaged public infrastructures. Therefore, numerous studies have proven the positive association between the availability of green infrastructures, namely green roofs, bioswales, and permeable pavements and their roles in minimizing stormwater runoff and flood risks in city area. However, there are limited studies which evaluate the economic worth of implementing these green infrastructures in preventing flash floods. Hence, it is vital to evaluate the potential long-term cost reductions from implementation of green infrastructure in flash flood mitigation to local authorities. Henceforth, this study aims to develop an economic model of the green infrastructure’s efficiency of green roof, permeable pavement, and bioswale in managing stormwater runoff. This study is conducted within the jurisdiction of Dewan Bandaraya Kuala Lumpur. It integrated data from systematic analysis from literature reviews and cost-benefit analysis based on interviews with local authorities to estimate the savings achieved through green infrastructure in flash flood management for local authorities. The findings show that the estimated cost savings by implementing green roof, permeable pavement and bioswale are approximately RM6,848, RM7,500 and RM6,875 per km² respectively. However, it is recommended to implement all three green infrastructures to maximize the overall effectiveness in reducing stormwater runoff and to achieve optimal cost savings from economic and environmental perspectives. This study is significant in promoting sustainable practices in infrastructure management and achieving the nation's Sustainable Development agenda.
Keywords: Green infrastructure, green roof, permeable pavements, bioswales, urban stormwater